Academic Senate Minutes 2015-04-16 - Academic Senate:::::::::
Agenda – Approved. Minutes of 4/2/15 – Approved. Questions for the President. CANDEL Discontinuance - First Reading. Provost Report. CFA Report. Statewide Senators Report. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. Special Guests: Steven Filling, Chair of the Statewide Senate and Stephen Stepanek, Faculty Trustee. Classroom Upgrades Report. EPC Report. FSAC Report. SAC Report. Good of the Order.